Mentoring at Girls Write Now - Bauer-Maglin, Nan (Radical Teacher, 2017)
Founded in 1998, Girls Write Now (GWN) mentors underserved high school girls from throughout New York City’s five boroughs—over 90% high need and 95% girls of color. GWN runs two programs for mentors and mentees: the Writing & Mentoring and Digital Media Mentoring programs. The Writing & Mentoring program currently has 180 people (90 mentees, 90 mentors) and the Digital Media Mentoring program has 100 people (50 mentees, 50 mentors). This article is about the writing program as that is the one I volunteer for.